Predictors of Treatment Access and Initiation Among Diverse, Low-Income Victims of Violence Offered a Trauma-Focused Evidence-Based Psychotherapy - Ghafoori, Bita (Journal of interpersonal violence, 2021)
Many victims of violence may benefit from trauma-focused evidence-based psychotherapies (EBPs), but fail to utilize treatment. The current study investigated factors associated with treatment access and treatment initiation in a low-income, racially and ethnically diverse, urban population of victims of violence who were screened for EBPs. The sample consisted of 941 adults, mean age = 35.87 (SD = 12.8), who were screened for mental health treatment and offered an EBP. Overall, 55.7% of individuals accessed treatment by attending an in-person screening appointment and intake, and 79.0% of the individuals who accessed treatment then initiated treatment by attending the first EBP session. Analysis revealed higher age (odds ratio [OR] = 1.05, 95% confidence interval (CI) = [1.04, 1.09]) and lower expression of posttraumatic stress disorder (PTSD) symptoms predicted higher rates of accessing treatment (OR = 0.20, 95% CI = [0.05, 0.82]). Higher global severity of distress (OR = 3.22, 95% CI = [1.14, 9.10]), poor quality of life in the area of psychological health (OR = 0.90, 95% CI = [0.81, 1.00]), and better quality of life in the area of physical health significantly predicted initiation of treatment (OR = 1.11, 95% CI = [0.998, 1.24]). Findings suggest that low-income, ethnically and racially diverse victims of violence may effectively utilize trauma-focused EBPs offered in a community setting.